Properties of concrete containing electric arc furnace steel slag and steel sludge. (March 2020) - Roslan, Nurul Hidayah; Ismail, Mohammad; Khalid, Nur Hafizah A.; Muhammad, Bala
Abstract: This paper presents an experimental study concerning the properties of concrete prepared with waste products generated from steel industry, namely electric arc furnace steel slag (EAFS) and steel sludge. A series of mixes with varying contents of EAFS or steel sludge up to 20% as cement replacement was prepared to assess several crucial aspects, such as workability, compressive strength, initial surface absorption test (ISAT), water absorption, and heavy metals of leaching test. Alteration on concrete microstructure was studied to determine the roles and the interaction mechanism with cement matrix. The experimental outputs signified that 10% replacement of EAFS and steel sludge with sufficient workability enhanced the compressive strength, especially in later age of concrete strength development. Both initial surface absorption and water absorption capacities were enhanced at similar percentage of replacement of EAFS and steel sludge, thus minimising permeability properties. Leaching test outcomes revealed that the inclusion of the two steel by-products into concrete did not pose any threat to the environment. The morphology evidence showed that concrete containing EAFS and steel sludge appeared denser as compared to normal concrete. Therefore, concrete containing EAFS and steel sludge possesses high potential for application in light of green and advanced concrete technology. Highlights: Inclusion of steel slag and sludge into concrete improve its properties. Mixes including steel sludge were observed to be less permeable than mixes with EAFS. Up to 20% of steel slag and steel sludge had effectively solidified and stabilised in cement matrix.